A Novel Use of Honey's Aggregation Approach to the Analysis of Repertory Grids. Issue 2 (May 2019) - Rojon, Céline; McDowall, Almuth; Saunders, Mark N. K.
This article examines and appraises a novel approach for generating shared group constructs through aggregative analysis: the application of Honey's aggregation procedure to repertory grid technique (RGT) data. Revisiting personal construct theory's underlying premises and adopting a social constructivist epistemology, we argue that, while "implicit theories" of the world, elicited via RGT, are unique to individuals, the constructs on which they are founded may be shared collectively. Drawing on a study of workplace performance, we outline a protocol for this novel use of Honey's approach, demonstrating how it can be utilized to generate shared constructs inductively to facilitate theory building. We argue that, unlike other grid aggregation processes, the approach does not compromise data granularity, offering a useful augmentation to traditional idiographic approaches examining individual-level constructs only. This approach appears especially suited to addressing complex and implicit topics, where individuals struggle to convey thoughts and ideas.